KAJIAN SOSIOLOGIS TENTANG EKSISTENSI PEREMPUAN DI TEPI SUNGAI KAPUAS, PONTIANAK – KALIMANTAN BARAT - Ismail Ruslan; Nunik Hasriyanti (PSGA LP2M IAIN Pontianak, 2018)
The writing of this article aims to reveal the existence of women on the banks of the Kapuas River, in the Pontianak area and its surroundings. This article is used is a qualitative method with a sociological approach. Based on the results of a study conducted by researchers, some interesting findings were obtained, including: 1) from the economic aspects of the community on the banks of the Kapuas River they always rely their lives on the natural resources of the Kapuas river; 2) from the aspect of gender, previously women were not justified and considered taboo to play a role in the public domain, they only served in domicile regions, now women have played a role and acted more freely in the public domain; and, 3) the continuation of the public role, the facts show that not a few women on the edge of the Kapuas River have shown achievements in all aspects of life, both social, economic, political, etc. [Penulisan artikel ini bertujuan untuk mengungkap tentang eksistensi perempuan di tepi sungai Kapuas, di wilayah Pontianak dan sekitarnya. Metode yang digunakan adalah metode kualitatif dengan pendekatan sosiologis. Berdasarkan hasil kajian yang dilakukan oleh peneliti, diperoleh beberapa temuan menarik, antara lain: 1) dari aspek ekonomi masyarakat pinggir Sungai Kapuas selalu menyandarkan kehidupan mereka pada sumber daya alam sungai Kapuas; 2) dari aspek gender, dahulu perempuan tidak dibenarkan dan dianggap tabu berperan dalam domain publik, mereka hanya bertugas dalam wilayah domistik, saat ini perempuan telah berperan dan berkiprah lebih leluasa dalam wilayah publik; dan, 3) kelanjutan dari peran publik itu, fakta menunjukkan bahwa tidak sedikit perempuan pinggir Sungai Kapuas yang telah menunjukkan prestasi dalam segala aspek kehidupan baik sosial, ekonomi, politik dan sebagainya].